2020
DOI: 10.3390/rs12101546
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vegetation Phenology and Productivity in Alaska Over the Past Two Decades

Abstract: Understanding trends in vegetation phenology and growing season productivity at a regional scale is important for global change studies, particularly as linkages can be made between climate shifts and the vegetation’s potential to sequester or release carbon into the atmosphere. Trends and geographic patterns of change in vegetation growth and phenology from the MODerate resolution Imaging Spectroradiometer (MODIS) satellite data sets were analyzed for the state of Alaska over the period 2000 to 2018. Phenolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…There is some evidence from both tundra and boreal systems that increases in peak productivity correspond with longer growing seasons and earlier green-up dates (Arndt et al 2019, Bergeron et al 2007). However, other studies have found spatial mismatches between greening and earlier start of season dates similar to what we found in the Bathurst range (Raynolds et al 2013, Potter andAlexander 2020). One potential explanation for this is that earlier and more rapid green-up in the spring depletes soil moisture reserves earlier in the growing season, which decreases maximum productivity later in the summer (Gonsamo et al 2019).…”
Section: Productivity and Phenology Trendssupporting
confidence: 86%
See 2 more Smart Citations
“…There is some evidence from both tundra and boreal systems that increases in peak productivity correspond with longer growing seasons and earlier green-up dates (Arndt et al 2019, Bergeron et al 2007). However, other studies have found spatial mismatches between greening and earlier start of season dates similar to what we found in the Bathurst range (Raynolds et al 2013, Potter andAlexander 2020). One potential explanation for this is that earlier and more rapid green-up in the spring depletes soil moisture reserves earlier in the growing season, which decreases maximum productivity later in the summer (Gonsamo et al 2019).…”
Section: Productivity and Phenology Trendssupporting
confidence: 86%
“…In any case, the spatial mismatch between the two trends in the range of the Bathurst herd explains why the prevalence of significant time integrated EVI trends (which integrates the two) was so much greater than it was for either one individually. Other studies that have examined additive or time integrated vegetation indices have found similarly high prevalence of significant positive trends in the tundra (Park et al 2016, Potter andAlexander 2020).…”
Section: Productivity and Phenology Trendsmentioning
confidence: 82%
See 1 more Smart Citation
“…Snow-free periods are 5–6 days longer per decade [ 4 , 8 ], and precipitation has increased about 1% per decade over the past 100 years [ 7 ], which influences not only depth, extent and persistence of snow cover [ 4 ], but also snow density and occurrence of rain-on-snow events [ 9 , 10 ]. Climate change also can indirectly affect wildlife populations at high latitudes by altering the composition of ecological communities [ 11 ], including expansion of shrubs into tundra and alpine habitats [ 12 , 13 ] and changes in plant phenology in arctic communities [ 14 , 15 ]. Understanding of the effects of climate change on arctic-adapted wildlife species via both direct and indirect pathways is advancing.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite observations indicate a 'greening' of tundra ecosystems (13,(15)(16)(17)(18)(19)(20) and shifts in growing season phenology over recent decades (21)(22)(23)(24) . Observations of increasing tundra greenness are often reported from surface-reflectance-derived Normalised Difference Vegetation Index (NDVI) (16,18,25,26) .…”
Section: Satellites Show Greening Of the Tundramentioning
confidence: 99%